PUBLIC AND PRIVATE AGENTS IN WATERWAY TRANSPORT DEVELOPMENT: THE EXPERIENCE OF WALLONIA (BELGIUM) - MORAIS, ARTUR; Aragão, Joaquim; Yamashita, Yaeko; Brasileiro, Anísio; Consulin, Ricardo (Archives of Business Research, 2020)
This article is part of the research efforts regarding policymaking processes in public policy and investments in infrastructure, especially in waterway transport. Previous papers have focused on analyzing the action of interest groups or coalitions in such policymaking processes, having established methodologies and field research programs. The field research reported here concerns the Belgian waterway system of the Walloon Region, and the policymaking processes regarding its management. After describing this waterway system and reporting its economic importance for the regional economy, we investigate the procedures adopted by policymakers in their management. By means of interviews with public and private agents, we found that the explanatory model of interest groups could not be validated in this case. On the other hand, a network of public and private agents was found working in close harmony to manage, expand and achieve the system’s economic success. At the same time, it was noted that the promotion of the waterway system is part of a broader strategy to ensure that the Walloon Region has a competitive logistics position at the heart of the European Union.